2014
DOI: 10.1111/1462-2920.12367
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium induces differential expression of methane and nitrogen metabolism‐related genes in Methylocystis sp. strain SC2

Abstract: Nitrogen source and concentration are major determinants of methanotrophic activity, but their effect on global gene expression is poorly studied. Methylocystis sp. strain SC2 produces two isozymes of particulate methane monooxygenase. These are encoded by pmoCAB1 (low-affinity pMMO1) and pmoCAB2 (high-affinity pMMO2). We used RNA-Seq to identify strain SC2 genes that respond to standard (10 mM) and high (30 mM) NH4(+) concentrations in the medium, compared with 10 mM NO3(-). While the expression of pmoCAB1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…The CH 4 fluxes showed a positive correlation with NH 4 + , and NH 4 + was selected as an indicator in the stepwise regression model ( Table 3 and Figure 3 ). A great many studies have revealed that NH 4 + has an inhibitory effect on CH 4 oxidization through either competition for methane monooxygenase or generation of toxic hydroxylamine and nitrite from ammonium oxidation (Steudler et al, 1989; Bosse et al, 1993; Dunfield and Knowles, 1995; Hanson and Hanson, 1996; Duan et al, 2013; Dam et al, 2014; Karbin et al, 2015), although stimulation effects or no effects of NH 4 + on methanotrophs were reported in some other studies (Dunfield et al, 1995; Delgado and Mosier, 1996; Dan et al, 2001; Krüger and Frenzel, 2003; Shrestha et al, 2010; Hu and Lu, 2015). The CH 4 fluxes were negatively related with narG but positively related with nosZ genes abundances, which might be due to the significant correlations of narG with pmoA genes ( r = 0.84, p = 0.005) and of nosZ genes with NH 4 + ( r = 0.76, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…The CH 4 fluxes showed a positive correlation with NH 4 + , and NH 4 + was selected as an indicator in the stepwise regression model ( Table 3 and Figure 3 ). A great many studies have revealed that NH 4 + has an inhibitory effect on CH 4 oxidization through either competition for methane monooxygenase or generation of toxic hydroxylamine and nitrite from ammonium oxidation (Steudler et al, 1989; Bosse et al, 1993; Dunfield and Knowles, 1995; Hanson and Hanson, 1996; Duan et al, 2013; Dam et al, 2014; Karbin et al, 2015), although stimulation effects or no effects of NH 4 + on methanotrophs were reported in some other studies (Dunfield et al, 1995; Delgado and Mosier, 1996; Dan et al, 2001; Krüger and Frenzel, 2003; Shrestha et al, 2010; Hu and Lu, 2015). The CH 4 fluxes were negatively related with narG but positively related with nosZ genes abundances, which might be due to the significant correlations of narG with pmoA genes ( r = 0.84, p = 0.005) and of nosZ genes with NH 4 + ( r = 0.76, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be that such methanotrophs can utilize multicarbon compounds for growth but that appropriate growth conditions that sufficiently enhance expression of required pathways have yet to be identified. For example, it has recently been shown that expression of the high-affinity form of the pMMO, but not the low affinity form, was downregulated in Methylocystis strain SC2 in the presence of elevated concentrations of ammonium (49). It may be that the presence of ammonium, or more generally the availability of nitrogen, also affects the expression of alternative carbon assimilation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally regarded that ammonium radicals were the competitive inhibitor of particular methane monooxygenase (pMMO) (He et al, 2017; Hu and Lu, 2015; Dam et al, 2014; Nyerges et al, 2010; Nyerges and Stein, 2009; Nyerges, 2008; Dunfield and Knowles, 1995; Schnell and King, 1994; Carlsen et al, 1991; Murrellt and Dalton, 1983), which will resulted in the lower growth of strains from methane. However, this study also proved that ammonium would hinder the growth of ZR1 from methanol, although its supposed competent object pMMO is not the key enzyme for the metabolism of methanol.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, ammonium was also identified to inhibit the growth of ZR1 from methanol and accumulate during the growing process. Recently, ammonium was reported to have effects on global gene expression of methane and nitrogen metabolism-related gene in methanotrophs (Dam et al, 2014). Being the nitrogen metabolic intermediate, accumulation of ammonium may have multiple effects on the growth of methanotrophs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation